EVALUASI KEEFEKTIFAN SUPERVISI KLINIK DI RUMAH SAKIT PENDIDIKAN UTAMA DAN JEJARING FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM SULTAN AGUNG SEMARANG - , DIAN APRILIANA RAHMAWATIE; , dr. Gandes Retno Rahayu, M.Med.Ed., PhD, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Clinical supervision has a vital role in the learning process of undergraduate medical education because it may improve the studentâs clinical performance of the students. Supervision is a complex activity and covers wide variety of applications. Medical faculty of Islamic Sultan Agung university has 15 affiliated hospital for its clinical education. To assure the quality of the clinical program, an evaluation on the quality of clinical supervision is required. Purpose: To assess the effectiveness of the clinical supervision among the 12 affiliated hospital and the correlation between the effectiveness clinical supervision and studentâs clinical competencies of the undergraduate clinical education. Methods: 181 students of clinical internship of the year 2003, 2004 and 2005 of medical faculty of Islamic sultan Agung university having the clinical rotation at the stage of surgery , obs-gyn, pediatrics, internal medicine ,ENT, psychiatry across the affiliated hospital. The subject were divided into groups based on the hospital they were placed. Clinical Teaching Effectiveness Instrument (CTEI) adapted in bahasa Indonesia was used. The clinical competency was the secondary data, i.e. final grade of every stage. Kruskal Wallis and Spearman rho were applied for the data analysis. Results: Means of the effectiveness of clinical supervision for 12 affiliated hospitals range from 3.25 to 4.02. Kruskal Wallis test resulted in the value of Chi-S=13.32 and p=0.27. Spearman correlation test between the clinical supervision and studentâs clinical competency of the ENT, obsgyn, pediatric, psychiatry, neurology, venerology, internal medicine, surgery were r=0.687 (p=0.010)